2008
DOI: 10.1108/02637470810913450
|View full text |Cite
|
Sign up to set email alerts
|

Designing out crime in Western Australia: a case study

Abstract: Purpose of this paper:To present developments in designing out crime policy in Western Australia (WA) as a case study example, discussing the innovative Designing Out Crime Strategy, a systematic attempt at embedding such ideas within government policy.Design / methodologies / approach: Report on the systems approach adopted by the WA government, which draws together three key themes of designing out crime, namely; the design of the built environment, the ongoing management of the built environment and the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Many police and local authority staff now receive CPTED training ( Kelpczarek, 2003 ;McDonald and Kitteringham, 2004 ;Cozens et al , 2008 ;Book and Schneider, 2010 ; McCauley and Opie, no date ); rating systems for some forms of built environment operate in some jurisdictions to quantify safety and security (for example, the Secured by Design accreditation process in the United Kingdom); CPTED practitioner professional associations have emerged (for example, the International CPTED Association); and many planning regimes incorporate CPTED design principles ( Australian Capital Territory Government, 2000 Government, 2007 ).…”
Section: Crime Prevention Through Environmental Designmentioning
confidence: 99%
“…Many police and local authority staff now receive CPTED training ( Kelpczarek, 2003 ;McDonald and Kitteringham, 2004 ;Cozens et al , 2008 ;Book and Schneider, 2010 ; McCauley and Opie, no date ); rating systems for some forms of built environment operate in some jurisdictions to quantify safety and security (for example, the Secured by Design accreditation process in the United Kingdom); CPTED practitioner professional associations have emerged (for example, the International CPTED Association); and many planning regimes incorporate CPTED design principles ( Australian Capital Territory Government, 2000 Government, 2007 ).…”
Section: Crime Prevention Through Environmental Designmentioning
confidence: 99%
“…Indeed, Designing Out Crime and CPTED ideas are being applied in the UK (Cozens et al, 2004), in Australia (Cozens et al, 2008) and at a global level (Schneider & Kitchen, 2007;Cozens, 2008c).…”
Section: Urban Planning and Environmental Criminologymentioning
confidence: 99%
“…Cozens et al (2005) reviewed the findings of place-based crime prevention research and concluded that crime prevention through environmental design (CPTED) is effective in reducing crime and fear of crime. Design guidelines and criteria for various urban spaces, including shopping centres, have been suggested (Cozens et al, 2008).…”
Section: Shopping Centre Attributesmentioning
confidence: 99%